2012
DOI: 10.1186/1745-6215-13-17
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cricoid pressure in preventing gastric aspiration during rapid sequence intubation in the emergency department: study protocol for a randomised controlled trial

Abstract: BackgroundCricoid pressure is considered to be the gold standard means of preventing aspiration of gastric content during Rapid Sequence Intubation (RSI). Its effectiveness has only been demonstrated in cadaveric studies and case reports. No randomised controlled trials comparing the incidence of gastric aspiration following emergent RSI, with or without cricoid pressure, have been performed. If improperly applied, cricoid pressure increases risk to the patient. The clinical significance of aspiration in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In emergency medicine, the efficiency of cricoid pressure to prevent aspiration still has to be documented 12. In addition, the use of cricoid pressure during emergent intubation might be associated with impaired laryngeal views 13.…”
Section: Discussionmentioning
confidence: 99%
“…In emergency medicine, the efficiency of cricoid pressure to prevent aspiration still has to be documented 12. In addition, the use of cricoid pressure during emergent intubation might be associated with impaired laryngeal views 13.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective, randomized trial compared two methods of CP application in patients undergoing RSI within the emergency departments (EDs) of two regional hospitals in NSW, Australia. The study protocol was registered (ACTRN12611000587909); full methodology was published and approved by the Hunter New England and the North Coast Area Health Service Human Research Ethics committees.…”
Section: Methodsmentioning
confidence: 99%
“…It involves the application of backward pressure on the cricoid cartilage with a force of between 30 and 40 N [1][2][3][4][5] in order to occlude the upper oesophagus (although latterly it has been suggested that a force of 20-30 N [6][7][8] might be more appropriate). Failure to secure the airway in this way may put the patient at risk of developing aspiration pneumonitis, bacterial pneumonia and or bronchial blockage [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although ubiquitous, numerous studies have shown that knowledge and skills of cricoid pressure amongst anaesthetic and emergency department staff are still quite poor [8][9][10][28][29][30][31][32]. The main deficiencies lie in the practitioners' method of application and understanding of the correct amount of force to apply [8,30].…”
Section: Introductionmentioning
confidence: 99%